The importance of early diagnosis of autism spectrum disorder for adequate treatment and rehabilitation in Macedonia - Petrusheva, Tea; Trajkovski, Vladimir (Specijalna edukacija i rehabilitacija, 2022)
Introduction. Autism spectrum disorder (ASD) has unclear etiology and no known universal treatment, making it difficult to obtain an accurate and timely diagnosis. The evidence that highlights the importance of early diagnosis and treatment is growing. Objective: The research was done to evaluate the impact of early diagnosis and its significance, as well as the effectiveness in obtaining the diagnosis in the past years and decades in Macedonia. Methods. We carried out a comparative analysis of the collected data from 95 subjects divided into three groups: 30 parents, 35 special educators and rehabilitators, and 30 members of the professional team that participated in diagnosing autism, using an original research tool in the form of three questionnaires. The data from the study refers to a research study conducted in Macedonia. Results. Many prenatal, perinatal, and postnatal factors can lead to ASD. The most common symptoms include: lack of speech, delayed speech for a specific age, not responding to their name, no eye contact, weak social skills, hyper/hyposensitivity, and isolation. Autism more frequently occurs isolated than accompanied by other conditions. The mean age of diagnosis used to be 5.6, while, in recent years, it has been 4.2. Children wait around 2.1 years from the first symptoms to obtain a diagnosis. Parents visit fewer institutions in the process of obtaining an ASD diagnosis. There is still a significant number of misdiagnoses. Conclusions. Many factors play a role in the occurrence of autism. There are a number of symptoms that appear in most cases. In the last decade, autism has been diagnosed earlier than before. The approach and process of diagnosing autism in Macedonia have improved.